Boosting budget absorption: How organizational commitment enhances budget implementation in Indonesian local government - La Ode Muhammad Saum Fasihu; Safaruddin Safaruddin; Muhammad Zaikin; Mutmainnah Mutmainnah; Nurul Emil Safitri (Privietlab, 2025)
This study aims to analyze the moderating effect of organizational commitment on budget implementation and absorption in Regional Apparatus Organizations in Southeast Sulawesi Province. The study population comprised all civil servants within the 30 Regional Apparatus Organizations in Southeast Sulawesi Province. Purposive sampling was employed to select participants based on their roles, knowledge, and experience. The sample criteria targeted five key leadership figures from each organization: the Head of Service, Secretary, Head of the Financial Subsection, Head of the Planning Subsection, and Treasurer. Consequently, a total sample of 150 respondents was obtained for this study. Data were collected using questionnaires from October to December 2024. The analysis was conducted using the SPSS 26 PROCESS macro (Version 4.3). The data analysis shows that budget implementation positively and significantly affects budget absorption. Organizational commitment significantly moderates budget implementation and absorption.